Correlation between Serum Calcium and In-Patient Mortality among Patients with Hemorrhagic and Non-Hemorrhagic Cerebrovascular Disease - Gautam, Rakshya; Mesina-Nepomuceno, Belinda Lioba L.; Paudel, Pratik (Annapurna Journal of Health Sciences, 2023)
Introduction: Cerebrovascular disease is the second most frequent cause of death worldwide. This study was designed to access the correlation between ionized calcium and clinical outcomes of Cerebrovascular events. Methods: The study included 225 cases diagnosed with cerebrovascular disease and undergone a CT scan. Calcium (ionized calcium) was measured within 1-2 hrs. Of sample collection. The time frame of the study was from December 2016 till December 2017.Result: Out of 225 participants the mean age of patients who have had infarction was higher compared to those who had haemorrhage (59.77±13.29 vs. 54.85±11.74, p value=0.097).Significant correlation was noted between hypertension and cerebrovascular disease . Also Significant difference between sex and type of cerebrovascular accidents was not established (p value =0.128)Conclusion: Serum calcium was found to be associated with clinical outcome among stroke patients found to have infarction. High incidence of favourable clinical outcome among those who have normal level of serum calcium compared to those who have low serum calcium level was found.